Natural moral law in contemporary society - Zaborowski, Holger, 1974- (Studies in philosophy and the history of philosophy, 2010)
"Natural law is a controversial subject but one of great significance in the ongoing and increasingly important discussion about the foundations of moral reasoning. The essays of this volume examine natural moral law, different natural law theories, and the role that natural law can and should play in our contemporary society. While some essays explore systematically the metaphysical and moral foundations of natural law, others focus on questions related to the application of natural law in the political, medical, or legal realm, or discuss historical questions that are closely related to the crisis and defense of natural law. All contributors agree that natural law is a concept that cannot and must not be dismissed and that is in need of a careful retrieval. While there are clearly differences in emphasis among the contributors, most of them also agree that the defense of natural law, the critique of the modern dismissal of natural law and of a modern non-teleological understanding of nature, and the proper use of philosophical reasoning are all closely related."--Jacket